A magmatic trigger for the Paleocene-Eocene thermal maximum? - Dubin, Andrea Rose (Massachusetts Institute of Technology, 2015)
Thesis: Ph. D., Joint Program in Chemical Oceanography (Massachusetts Institute of Technology, Department of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2015. Cataloged from PDF version of thesis. Includes bibliographical references. Fifty-six million years ago Earth experienced rapid global warming (~6°C) that was caused by the release of large amounts of carbon into the ocean-atmosphere system. This Paleocene-Eocene Thermal Maximum (PETM) is often cited as an analogue of anthropogenic climate change. Many trigger mechanisms for the carbon release at the PETM have been proposed. Common to all scenarios is rapid release of isotopically light carbon (<¹³C/¹²C values) from methane hydrates, terrestrial or marine organic matter, as indicated by a pronounced excursion to light carbon isotope values across the PETM. I test the hypothesis that the PETM warming and isotope excursion were caused by the intrusion of a magmatic sill complex into organic-rich sediments in the North Atlantic. The intrusion of magma into sedimentary rocks will cause heating and metamorphic reactions in a thermal aureole around the intrusion. If these sediments are rich in organic matter, large volumes of isotopically light carbon are rapidly released. I examine geochemical evidence from lead, osmium, and organic carbon to place constraints on the extent the carbon isotope excursion during the PETM may have been caused by contact metamorphism of organic-rich sediments. Potential terrestrial and submarine analogs are examined to determine the behavior of these elements during thermal alteration. Furthermore, geochemical evidence from sediment cores at the PETM provides additional information about what might have caused the carbon isotope excursion. I find that lead is not a suitable proxy for carbon mobilization to the overlying seawater during contact metamorphism. Osmium, however, is mobilized together with carbon. Making reasonable assumptions for the ¹⁸⁷Os/¹⁸⁸Os of the sediments from ...